Modelling of surfactants and chemistry for electroless Ni-P plating. (3rd June 2018) - Farzaneh, Amir; Ehteshamzadeh, Maryam; Cobley, Andrew J.
ABSTRACT: In this work, the effects of the chemical formulation in an electroless nickel phosphorus electrolyte on the physical and mechanical performance of the obtained coating were evaluated. The study not only paid particular attention to the concentration and type of surfactant (anionic, cationic and non-ionic) but also investigated the effect of pH and concentration of sodium hypophosphite in the electrolyte. A three-level Box–Behnken factorial design related to response surface methodology was employed to model the effect of the mentioned parameters and optimise the properties of the coating. Two models fitted with experimental data obtained from microhardness and thickness measurement of the Ni-P coatings. The optimum conditions were determined at pH = 5 with 32 g L −1 sodium hypophosphite and 1.5 g L −1 anionic surfactant. According to the derived models, this formulation would give a Ni-P coating with a microhardness of 1080 Hv and a thickness of 23 µm.